DO THE EDUCATIONAL SERVICE CHARACTERISTICS AND PERCEPTIONS MATTERS TO INTENTION TO RECRUIT MASTER OF MANAGEMENT’S ALUMNI IN CENTRAL JAVA? - Liza Agustina Maureen Nelloh (Jurnal Manajemen Pemasaran, 2010)
Competitiveness arena of higher education in Central Java Indonesia motivates its institution to improve branding strategy, and the quality of its educational characteristics in order to build good perception about its institution and the quality of its graduate. The author focuses on several perceptions’ dimensions to evaluate educational service characteristics such as brand awareness, quality of the graduates, and institutional image. Whether those variables will positively impact on intention to recruit, the author wants to see the correlation of each variables simultaneously using Structural Equation Model (SEM). Data were collected through purposive sampling in several cities in Central Java. Owners and managers from several industries were asked to evaluate Satya Wacana Christian University, especially its Master of Management program. The results indicate all hypothesizes were supported by data. This study contributes to branding strategy in higher education and present important insight to improve several education qualities in higher education sector.